2012
DOI: 10.3109/08923973.2012.663759
|View full text |Cite
|
Sign up to set email alerts
|

Overdose of Vinblastine in place of Vinorelbine during IGEV chemotherapy

Abstract: Any class of drugs is susceptible to errors, in case of antineoplastic agents the medication errors may cause severe and life-threatening toxicity due to very limited therapeutic index with toxic events even at therapeutic dosage, to complexity of regimens and the particular vulnerable population. We report herein a case of Vinblastine (VBL) accidental overdose, the cause of mistake, the toxic effect and the salvage therapy adopted in a young lady suffering of Hodgkin relapse during IGEV chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The organ coefficients of liver in the VBL–NPs–PEG–FA group were 7.33 ± 0.30, 6.78 ± 0.74, and 6.41 ± 0.30, respectively, on the 10th, 18th, and 26th days, which had no significant difference with the NS group (7.51 ± 0.52, 7.32 ± 0.45, and 6.91 ± 0.64) ( P > 0.05), whereas the VBL injection group (6.64 ± 0.45, 6.36 ± 0.32, and 6.06 ± 0.22) showed obvious lower values than the NS group ( P < 0.01). It was reported that vinblastine is hepatotoxic, , which may be connected with the liver metabolism of VBL . The spleen in the VBL group showed abnormal enlargement, and the organ coefficient (1.61 ± 0.44, 1.93 ± 0.33, 1.73 ± 0.26) was significantly higher than that in the NS group (1.07 ± 0.35, 1.22 ± 0.59, 1.01 ± 0.30) ( P < 0.05) and in the VBL–NPs–PEG–FA group (0.97 ± 0.18, 0.88 ± 0.09, 0.84 ± 0.19) ( P < 0.01) on the 10th, 18th, and 26th days.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The organ coefficients of liver in the VBL–NPs–PEG–FA group were 7.33 ± 0.30, 6.78 ± 0.74, and 6.41 ± 0.30, respectively, on the 10th, 18th, and 26th days, which had no significant difference with the NS group (7.51 ± 0.52, 7.32 ± 0.45, and 6.91 ± 0.64) ( P > 0.05), whereas the VBL injection group (6.64 ± 0.45, 6.36 ± 0.32, and 6.06 ± 0.22) showed obvious lower values than the NS group ( P < 0.01). It was reported that vinblastine is hepatotoxic, , which may be connected with the liver metabolism of VBL . The spleen in the VBL group showed abnormal enlargement, and the organ coefficient (1.61 ± 0.44, 1.93 ± 0.33, 1.73 ± 0.26) was significantly higher than that in the NS group (1.07 ± 0.35, 1.22 ± 0.59, 1.01 ± 0.30) ( P < 0.05) and in the VBL–NPs–PEG–FA group (0.97 ± 0.18, 0.88 ± 0.09, 0.84 ± 0.19) ( P < 0.01) on the 10th, 18th, and 26th days.…”
Section: Resultsmentioning
confidence: 87%
“…It was reported that vinblastine is hepatotoxic, 79,80 which may be connected with the liver metabolism of VBL. 81 The spleen in the VBL group showed abnormal enlargement, and the organ coefficient (1.61 ± 0.44, 1.93 ± 0.33, 1.73 ± 0.26) was significantly higher than that in the NS group (1.07 ± 0.35, 1.22 ± 0.59, 1.01 ± 0.30) (P < 0.05) and in the VBL−NPs−PEG−FA group (0.97 ± 0.18, 0.88 ± 0.09, 0.84 ± 0.19) (P < 0.01) on the 10th, 18th, and 26th days. Interestingly, no significant difference was observed between VBL−NPs−PEG−FA and NS groups on the organ coefficient of spleen (P > 0.05).…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%